Corporate social responsibility: Institutional legitimacy action and strategy - Abdul Hamid, Fathilatul Zakimi; Atan, Ruhaya (2012)
The objective of the study is to investigate the Corporate Social Responsibility (CSR) action and strategy used by the top 100 Malaysian Listed Companies followings the 1997 Asian's financial crisis. This research focus on Malaysian companies because Malaysia considered as one of the largest stock market in Southeast Asia countries. These studies utilize company's annual reports as a proxy for their CSR initiatives. As crisis has resulted negative impact to country and society, the result of the study shows that the economic crisis have motivated government and business to joint hand together to mitigate the impacts, as evident since 1920s i.e. after the Stock Market crash in United States and World War II. On the other hand, the crisis has also provide opportunity for the business to redirect away from a threat to an opportunity that differentiate them from the others. Furthermore, the study fairly explains legitimacy theory notions on the managerial actions from the Institutional lens namely "Institutional Legitimacy". Finally, apart from offerings descriptive contribution, our ambition is to assist future research on the post economic crisis particularly after the 2008 global economic crisis. This is because the state social structures, communities and people's ways of life were completely re-shaped after the economic changes.